Asthma Diagnosis and Airway Bronchodilator Response in HIV-infected Individuals - Gingo, Matthew R. (2011)
BACKGROUND: Despite the high prevalence of respiratory symptoms and obstructive lung disease in HIV-infected persons, the prevalence of bronchodilator reversibility (BDR) and asthma has not been systematically studied during the era of combination antiretroviral therapy (ART). OBJECTIVE: To determine the prevalence of asthma diagnosis and related pulmonary function abnormalities in an HIV-infected cohort and to identify potential mechanisms. METHODS: A cross-sectional analysis of 223 HIV-infected individuals with data on respiratory symptoms and diagnoses, pulmonary function, sputum cell counts, and asthma-related cytokines and chemokines in serum/sputum. RESULTS: Doctor-diagnosed asthma was present in 46 (20.6%) and BDR (≥200ml and ≥12% increase in FEV(1) or FVC) in 20 participants (9.0%). Pulmonary symptoms and function were worse in those with doctor-diagnosed asthma. Doctor-diagnosed asthma was independently associated with female sex (p=0.04), body mass index >29.6kg/m(2) (vs.<29.6kg/m(2)) (p=0.03), history of bacterial or Pneumocystis pneumonia (p=0.01), and with not currently taking ART (p=0.04), and in univariate analysis with parental history of asthma (n=180; p=0.004). High sputum eosinophil percentages (>2.3% based on the highest decile) were more likely in those with doctor-diagnosed asthma (p=0.02) or BDR (p=0.02). Doctor-diagnosed asthma tended to be more common with high sputum IL-4 (p=0.02) and RANTES (p=0.02), while BDR was associated with high plasma macrophage inflammatory protein (MIP)-1α (p=0.002), and sputum MIP-1β levels (p=0.001). CONCLUSION: Asthma diagnosis and BDR are prevalent in an HIV-infected outpatient cohort, and associations with family history, obesity, allergic inflammation, prior infection, the absence of ART, and elevated HIV-stimulated cytokines suggest possible mechanisms of HIV-associated asthma.